The Ever Cruel Kingdom - Book 2 - Chupeco, Rin; Allyn, Virginia (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2020)
"After a treacherous journey and a life-shattering introduction to a twin neither knew she had, sisters Haidee and Odessa expected to emerge from the Great Abyss to a world set right. But though the planet is turning once again, the creatures of the abyss refuse to rest without another goddess's sacrifice. To break the cycle, Haidee and Odessa need answers that lie beyond the seven gates of the underworld, within the Cruel Kingdom itself. The shadows of the underworld may hunger to tear them apart, but these two sisters are determined to heal their world--together"--
Keywords: Goddesses -- Juvenile fiction; Twins -- Juvenile fiction; Sisters -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Sacrifice -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Goddesses -- Fiction; Twins -- Fiction; Sisters -- Fiction; Mothers and daughters -- Fiction; Sacrifice -- Fiction; Voyages and travels -- Fiction; Fantasy; Fantasy fiction